2018
DOI: 10.1139/cjfr-2018-0132
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of ground flora response to fire in thinned PinusQuercus stands

Abstract: The ground flora stratum affects stand structure, resource acquisition, nutrient cycling, and taxonomic richness in forest ecosystems. Disturbances such as thinning and prescribed fire alter forest understory growing conditions that generally increase ground flora cover and richness. We studied annual changes in ground flora assemblages over three growing seasons after fire in thinned and frequently burned (3-year rotation) Pinus-Quercus stands. Our results corroborated trends from other studies that indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 64 publications
0
9
2
Order By: Relevance
“…Nonetheless, our results contradict much existing research that report decreases in red maple stem density following one or two prescribed burn treatments [35,60,61]. This may be because most red maple regeneration occurred from basal resprouts, resprout clumps insulated inner stems from fire damage, fires were not hot enough, or frequent dormant season burning may be creating more favorable microsite conditions for red maple by decreasing the litter and duff layers and allowing root growth into mineral soil [38,62,63]. Red maple responded least-favorably to C and MB, suggesting slowed growth from competition of other understory hardwoods in C, as represented by the changes of IV, or mortality after repeated mechanical reductions and/or increased fire severity in MB which may facilitate adequate control of this species.…”
Section: Mesic Hardwoodscontrasting
confidence: 88%
“…Nonetheless, our results contradict much existing research that report decreases in red maple stem density following one or two prescribed burn treatments [35,60,61]. This may be because most red maple regeneration occurred from basal resprouts, resprout clumps insulated inner stems from fire damage, fires were not hot enough, or frequent dormant season burning may be creating more favorable microsite conditions for red maple by decreasing the litter and duff layers and allowing root growth into mineral soil [38,62,63]. Red maple responded least-favorably to C and MB, suggesting slowed growth from competition of other understory hardwoods in C, as represented by the changes of IV, or mortality after repeated mechanical reductions and/or increased fire severity in MB which may facilitate adequate control of this species.…”
Section: Mesic Hardwoodscontrasting
confidence: 88%
“…Our results corroborate with the ones found by Fernandes et al [52], who in the study of E. globulus seed germination after soil disturbances, found higher germination in raked (~34%) than in unraked areas (~19%). Although there may be times when leaf litter facilitates germination because of its ability to hold moisture [32,53], the relationships we observed between germination rates and light availability (both canopy and litter light penetration) suggest that leaf litter is more of a hindrance to seed germination.…”
Section: Discussionmentioning
confidence: 68%
“…Agricultural land uses include heavy land management tactics, such as herbicide application and species control [30], that are not conducive to the establishment of non-native tree species. Forest-use lands and less extensively managed fields exhibit increased leaf litter and decreased light penetration [31,32], which are also not conducive to non-native tree establishment. Eucalyptus species are more likely to become invasive in lands that are managed with prescribed burns [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Vander Yacht et al (2017 b ) report that fire following light thinnings, where basal areas exceeded 15 m 2 /ha (>80% canopy closure), creates conditions that often maintain a woody‐dominated groundlayer, whereas heavy overstory removal to levels below that threshold followed by fire may stimulate the seed bank, which coupled with a higher light environment, facilitates an increase in the richness, diversity, and total cover of herbaceous and graminoid components. Burning after thinning can further promote and/or maintain the herbaceous (forb plus graminoid) component over time (Willson et al 2018; Barefoot et al 2019; Bassett et al 2020). In contrast, Oakman et al (2019) reported a negligible change in herbaceous or graminoid cover and diversity after thinning and four dormant season burns that together reduced overstory basal area (stems >10 cm dbh) to approximately 15 m 2 /ha in a mixed‐oak forest similar to and within proximity (approximately 60 km) to our study site.…”
Section: Discussionmentioning
confidence: 99%